2016
DOI: 10.1227/neu.0000000000001378
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Cost of Potentially Avoidable Transfers to a Tertiary Care Neurosurgery Service

Abstract: Background Thousands of neurosurgical emergencies are transferred yearly to tertiary care facilities to assume a higher level of care. Several studies have examined how neurosurgical transfers influence patient outcomes, but characteristics of potentially avoidable transfers have yet to be investigated. Objective To identify whether potentially avoidable transfers represent a significant portion of transfers to a tertiary neurosurgical facility. Methods In this cohort study, we evaluated 916 neurosurgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 21 publications
(21 reference statements)
1
33
0
Order By: Relevance
“…6 Kuhn et al identified a group of potentially avoidable transfer patients who in retrospect did not require additional workup or neurosurgical intervention and found that 70% of these patients had been admitted to the ICU. 8 In our cohort, 12% of patients admitted to the ICU did not have documented ICU needs and were transferred to a lower level of care within 24 hours. ED transfers had a higher rate of ICU admissions, as our practice is to err toward a higher level of care for patients referred from an ED since they have not been evaluated by a neurosurgeon and may still require additional imaging or medical workup.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…6 Kuhn et al identified a group of potentially avoidable transfer patients who in retrospect did not require additional workup or neurosurgical intervention and found that 70% of these patients had been admitted to the ICU. 8 In our cohort, 12% of patients admitted to the ICU did not have documented ICU needs and were transferred to a lower level of care within 24 hours. ED transfers had a higher rate of ICU admissions, as our practice is to err toward a higher level of care for patients referred from an ED since they have not been evaluated by a neurosurgeon and may still require additional imaging or medical workup.…”
Section: Discussionmentioning
confidence: 89%
“…13 Kuhn et al found that the direct transportation costs of avoidable transfers amounted to $1,460,000 over 2 years. 8 Although our study did not address the issue of avoidable transfers in detail, novel approaches and transfer management algorithms are needed to optimize the transfer request system. Kuhn et al retrospectively identified a subgroup of transfer patients who did not require neurosurgical diagnostic testing, intervention, or intensive monitoring after transfer, which accounted for nearly 20% of all transferred patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The care provided at the tertiary spine care level requires the highest resource intensity and should be limited to those few cases which cannot be managed at the primary and secondary spine care levels. The inappropriate referral to tertiary care can result in significant and unnecessary excessive cost and use of resources associated with such referrals [38].…”
Section: Tertiary and Quaternary Spine Carementioning
confidence: 99%